Judaism as Philosophy Studies in Maimonides and the Medieval Jewish Philosophers of Provence - Kreisel, Howard (Emunot: Jewish Philosophy and Kabbalah, 2015)
The studies comprising this volume, most of them appearing for the first time in English, deal with some of the main topics in Maimonides' philosophy and that of his followers in Provence. At the heart of these topics lies the issue of whether they adopted a completely naturalistic picture of the workings of the world order, or left room for the volitional activity of God in history. These topics include divine law, creation, the Account of the Chariot, prophet and sage, Mosaic prophecy, reasons for the commandments, and prayer. Special attention is paid to three lesser known but highly significant Provençal Jewish thinkers: Moses Ibn Tibbon, Levi ben Avraham, and Nissim ben Moses of Marseille.